Shopping Lifestyle, Fashion Involvement, Hedonic Shopping Motivation, Positive Emotion, Impulse Buying E-Commerce - Ni Wayan Reisma Ratna Dewi; I Nyoman Rasmen Adi (PT Mattawang Mediatama Solution, 2023)
Currently, Indonesian people use the internet to buy goods through e-commerce. This study aims to determine the influence of shopping lifestyle, fashion involvement, and hedonic shopping motivation on positive emotion and impulse buying on Tokopedia e-commerce. The data analysis techniques used are inferential analysis using SEM-PLS and descriptive analysis. The findings of this study show that shopping lifestyle, fashion involvement, and hedonic shopping motivation have a significant positive influence on positive emotions. Shopping lifestyle and fashion involvement have a significant positive influence on impulsive buying. However, hedonic shopping motivation has no influence on impulsive buying. Then, positive emotion has a positive and significant influence on impulsive buying. Positive emotion also mediates partial the relationship between shopping lifestyle, fashion involvement, and hedonic shopping motivation mediates perfect to impulsive buying.